Formation of Research Skills - Bernotas, Vytautas (Acta Paedagogica Vilnensia, 1991)
Formation of research skills is the way of organizing the student creative activities of the students as to independently solve practical problems of acquiring new knowledge. In this article research skills are viewed from the historical aspect. Thoughts of J. A. Komensky, Jean-Jacques Rousseau, John Dewey, and other classics of pedagogy on the subjects of research skills are discussed. It is noted that most of these ideas have not lost their importance in the present day school. Emphasizing that the problem of the formation of research skills can be successfully solved only when students have a demand for knowledge, have mastered the methods of scientific research, are able to raise different problems and are able to find their optimal solutions. The stages of the formation of research skills are discussed, specifics of each of them is shown. Also the possibilities of the formation of research skills both in classroom and extra-curricular activities. It is stated that the students will be able to successfully form research skills when this work will be integrated with the entire educational process, lessons of various subjects, homework, extra-curricular activities, the activities of lore and other clubs, student organizations, schools, libraries, when entire teaching staff, not just one or several teachers, are involved, and when the work is well coordinated.